Ancient vertebrate dermal armor evolved from trunk neural crest - Stundl, Jan; Martik, Megan L; Chen, Donglei; Raja, Desingu Ayyappa; Franěk, Roman; Pospisilova, Anna; Pšenička, Martin; Metscher, Brian D; Braasch, Ingo; Haitina, Tatjana; Cerny, Robert; Ahlberg, Per E; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Bone is an evolutionary novelty of vertebrates, likely to have first emerged as part of ancestral dermal armor that consisted of osteogenic and odontogenic components. Whether these early vertebrate structures arose from mesoderm or neural crest cells has been a matter of considerable debate. To examine the developmental origin of the bony part of the dermal armor, we have performed in vivo lineage tracing in the sterlet sturgeon, a representative of nonteleost ray-finned fish that has retained an extensive postcranial dermal skeleton. The results definitively show that sterlet trunk neural crest cells give rise to osteoblasts of the scutes. Transcriptional profiling further reveals neural crest gene signature in sterlet scutes as well as bichir scales. Finally, histological and microCT analyses of ray-finned fish dermal armor show that their scales and scutes are formed by bone, dentin, and hypermineralized covering tissues, in various combinations, that resemble those of the first armored vertebrates. Taken together, our results support a primitive skeletogenic role for the neural crest along the entire body axis, that was later progressively restricted to the cranial region during vertebrate evolution. Thus, the neural crest was a crucial evolutionary innovation driving the origin and diversification of dermal armor along the entire body axis.
Keywords: Animals; sterlet sturgeon; biologická evoluce; osteogeneze; scales; Fishes; Neural Crest; ryby; vertebrate evolution; Skull; Vertebrates; neural crest; obratlovci; lebka; Osteogenesis; zvířata; Biological Evolution; crista neuralis; skeleton